Treatment Options for COVID-19: A Review - Ali, Mukarram Jamat; Hanif, Muhammad; Haider, Muhammad Adnan; Ahmed, Muhammad Umer; Sundas, FNU; Hirani, Arham; Khan, Izhan Ali; Anis, Khurram; Karim, Amin H. (Frontiers in Medicine, 2020)
Abstract Background The recent COVID-19 pandemic sweeping the globe has caused great concern worldwide. Due to the limited evidence available on the dynamics of the virus and effective treatment options available, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a huge impact in terms of morbidity and mortality. The economic impact is still to be assessed. Aims The purpose of this article is to review the evidence for the multiple treatment options available, to consider the future of this global pandemic, and to identify some potential options that could revolutionize the treatment of COVID-19. Moreover, this article underscores the sheer importance of repurposing some of the available antiviral and antimicrobial agents that have been in use for long, to have an effective and expeditious response to this wide spreading pandemic; and the need to conduct multicenter global randomized controlled trial to reach an effective single anti-viral agents or a cocktail of available antimicrobial agents. Method We thoroughly searched and reviewed various case reports, retrospective analyses, and in vitro studies published in PubMed, EMBASE, and Google Scholar regarding the treatment options used for SARS-CoV, MERS-CoV, and SARS-CoV-2 since its outbreak, in an attempt to highlight treatments with the most promising results. Conclusion We are currently facing one of the worst pandemics in history. Compared to SARS-CoV and MERS-CoV, although SARS-CoV-2 is associated with lesser mortality rate however, higher infectivity of SARS-CoV-2 is making it a far more serious threat. Unfortunately, no vaccine against SARS-CoV-2, or an effective drug regimen for COVID-19, currently exists. The drug repurposing of available antiviral agents may provide a respite; moreover, a cocktail of antiviral agents may be helpful in treating this disease. Here, we have highlighted a few available antimicrobial agents that could be very effective in treating COVID-19, and a number of trials are underway to detect and confirm the efficacy of these agents.